2011
DOI: 10.1016/j.sdentj.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Lateral cephalometric norms for Saudi adults: A meta-analysis

Abstract: Orthodontic diagnosis and treatment planning require careful evaluation of the patient's cephalometric values and comparison to known population cephalometric means or norms. Despite the availability of several published studies on Saudi cephalometric norms, Caucasian norms are still referred to when Saudi patients are treated. To reach a consensus between these studies and to establish more accurately cephalometric norms for Saudis, a meta-analysis of the relevant literature was performed. Electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…[2][3][4][5]8,[38][39][40]42 Overall, Arab Omanis were found to have a more retruded maxilla when compared to the Eastman Standard norms or Egyptian, Saudi, Kuwaiti and Emirati samples; however, they were less retruded than Jordanian, Moroccan and Yemeni samples. [3][4][5]8,[38][39][40]42 Nevertheless, results from the present study showed no significant difference with Eastman Standard norms regarding the sagittal relationship between the maxilla and the mandible (i.e. the ANB angle).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…[2][3][4][5]8,[38][39][40]42 Overall, Arab Omanis were found to have a more retruded maxilla when compared to the Eastman Standard norms or Egyptian, Saudi, Kuwaiti and Emirati samples; however, they were less retruded than Jordanian, Moroccan and Yemeni samples. [3][4][5]8,[38][39][40]42 Nevertheless, results from the present study showed no significant difference with Eastman Standard norms regarding the sagittal relationship between the maxilla and the mandible (i.e. the ANB angle).…”
Section: Discussionmentioning
confidence: 87%
“…10,13 In addition, Omanis had the greatest degree of incisor proclination compared to other Arab populations, apart from Emiratis. [2][3][4][5]8,[38][39][40]42 Protrusion of the LI and the distance between the LI and facial plane was also increased by 1.8 mm and 1.5 mm, respectively. 22,23 This finding is in accordance with other studies of Arab populations which indicated greater proclined incisor relations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Variables such as gender and ethnic origin have different characteristics of skeletal, dental and soft tissue normality, which require knowledge of what is considered normal or standard in each ethnic group [1][2][3][4] . In addition, patients expect results to be in accordance with social and cultural standards of beauty prevalent in their reference group, the Zeitgeist, as well as in society in general 5 .…”
Section: Introductionmentioning
confidence: 99%